Comparison of LabUMat-with-UriSed and iQ®200 fully automatic urine sediment analysers with manual urine analysis - Akin, Okhan Kadir; Serdar, Muhittin A.; Cizmeci, Zeynep; Genc, Ozlem; Aydin, Suleyman (Portland Press Ltd, 2009)
Urine analysis is one of the most common tests for assessing urinary-tract and kidney diseases. In recent years there have been new developments in the automation of this test. The objective of the present study was to compare the performances of two urine sediment analysers, namely LabUMat with UriSed (77 Elektronika Kft, Budapest, Hungary) and iQ (R) 200 (Iris Diagnostics, Chatsworth, CA, U.S.A.), with the KOVA (R) method for manual urine measurement by evaluating the results in terms of similar parameters (cells or particles per lower-power field or high-power field). The results obtained using the UriSed and iQ (R) 200 analysers were more reproducible (7.1-30.2 and 14.9-35.4% respectively) than those obtained using the manual technique (17.9-44.4%). Significant correlations were established among the three techniques in the evaluation of leucocytes, erythrocytes and epithelial cells. Although the UriSed, iQ (R) 200 and visual-microscopic measurements were in agreement, confirmation of the results from automated methods by manual urine analyses is significantly useful, especially for pathological cases that were close to the limits of the techniques.
Keywords: fully automatic urine sediment analysis; iQ (R) 200 urine analyser; KOVA (R) system; LabUMat with UriSed urine analyser; visual manual urine sediment analysis